The spire a novel - Patterson, Richard North (New York Henry Holt and Co., 2009)
Mark Darrow returns to Caldwell College 16 years after his graduation when his mentor, Lionel Farr, brings him back to become Caldwell's president. The school is still haunted by the tragic murder of Angela Hall, an African American student who was strangled and left outside the school's landmark spire. Fresh off a football victory, Mark was the one who found Angela, and it was his best friend, Steve, who was convicted of the murder. Now Caldwell is once again facing a scandal, but Mark can't forget Angela's murder, or the nagging feeling that his friend might be innocent. As his suspicions center on a former classmate who testified against Steve, Mark finds himself falling for Farr's daughter, Taylor, the first woman he's had serious feelings for since the death of his wife two years ago.
Keywords: African American students -- Crimes against -- Fiction; Psychological fiction; Suspense fiction